Stress, coping and safety compliance in a multinational gold mining company. Issue 2 (3rd April 2017) - Jacobs, Melissa; Pienaar, Jacobus
Abstract : The primary objective of this study was to investigate the relationship of work stress, consisting of role stressors and job insecurity, with safety compliance at work. A secondary objective was to test for the possible moderating effect of individual employees' coping behaviour between experienced work stress and job insecurity, and their safety compliance. A cross-sectional survey design was used ( n = 771). An electronic survey, with a biographical questionnaire and scales on role conflict, role ambiguity, role overload, job insecurity, coping and safety compliance at work, was administered. The results indicated that specific aspects of work stress, notably role conflict, role ambiguity and quantitative job insecurity, and of coping, namely an avoidance style and changing the situation, were important in understanding safety compliance. A moderating effect of avoidance coping was also found.